沈降反応によるトウモロコシ類縁関係判別法に関する研究 : 第5報 自殖系統間に於ける Heterosis と沈降反應の程度に就て - 浦野 啓司; 荒井 好邦 (日本作物學會紀事, 1956)
In the previous report, URANO, one of the authors, has reported on the difference in protein constituents of the extract of pollen and on the close relation between the difference and the precipitin reaction. Now, in the corn plant, it has been assumed that heterosis is more remarkable when the parent plants are remotely related than when they are closely related. In the present paper the authors concern the relation between the heterosis and the precipitin reaction. The results of experimental studies done are as follows : (1) Nine single crosses of corn plants were used as material. (2) Correlation coefficients between the grade in precipitin reactions of the parent lines and the extent of heterosis in F_1 represented by its grain yield were = -0.430±0.3412 by judgement of precipitation with nakedeyes, and - 0.921±0.1473 by that with chemical analysis. While the coefficient obtained by using the weights of the F_1 whole plants was r = -0.753±0.2458. (3) Thus, by means of precipitin tests we may estimate the intensity of heterosis indirectly. If we recognize the fact that higher heterosis is usually obtained between the inbred parents of a more remote relationship, it may be possible to diagnose the latter in the corn plant by the precipitin method iustead of the crossing test.